Ser como el bambu = Be like the bamboo - Cala, Ismael; Suarez, Yunior (Nashville, Tennesse : HarperCollins Espanol, 2015)
Adorablemente ilustrado, este libro ensena a los ninos sobre las muchas propiedades del bambu en una tierna y dulce historia. Una buena manera para que padres e hijos convivan a la vez que fomentan el habito de la lectura con un valioso y entretenido mensaje. Este libro permite que los ninos aprendan jugando.
"I want to be tall, strong and flexible like the bamboo!", Baby Panda says to his mom. A bilingual book Spanish-English, beautifully illustrated, for children to learn the value of patience. --Page 4 of cover.
Text in Spanish and English.
Keywords: Pandas -- Juvenile fiction; Bamboo -- Juvenile fiction; Patience -- Juvenile fiction; Pandas -- Novela juvenil; Bambu -- Novela juvenil; Paciencia -- Novela juvenil; Spanish language materials -- Bilingual -- Juvenile literature; Materiales bilingues en espanol -- Literatura juvenil